Mathematical Analysis of the Impact of Real Exchange Rate on Output Growth and Inflation: The Case of Tanzania Zanzibar - Said, Khamis Khalid; Luvanda, Eliab; Massawe, Estomih S (International Journal of Mathematical Research, 2013)
This paper examines the dynamic relationship between stationary time series for the impact of real exchange rate on output growth and inflation in Tanzania: Zanzibar using vector autoregressive (VAR) model. The impact of the real exchange rate on economic performance in Tanzania using VAR approach shows that the main sources of variance decomposition in the volume of tourism and inflation are in their own shocks. Impulse response functions analysis show that the response generated by itself at short run and vanishing at the long run, and the inflation and number of tourism has no instantaneous impact on the first difference of real exchange rate. Variance decomposition analysis show that the impact of number of tourism arrival on real exchange rate increases monotonically to the long-run. Thus analysis show that 98 percent of the variance of number of tourism arrival is generated by its own innovations, while only 87 percent of the variance of inflation is generated by its own innovations and about 99 percent of the variance of real exchange rate generated by its own innovations. Furthermore; the real exchange rate is Granger causal to both inflation and number of tourism, while the number of tourism is Granger Causal to the inflation.